Navigating the Challenges and Seizing Opportunities in Implementing Closed-Loop Supply Chains - Abdelmhmud, Mohamed Azeem El Fatih (Journal of Ecohumanism, 2024)
Closed-Loop Supply Chains (CLSCs) present a transformative solution for industries seeking sustainability by reintegrating returned products through recycling, refurbishment, and remanufacturing, reducing waste and dependency on added resources. While offering substantial benefits, CLSC adoption faces challenges, including high infrastructure costs, complex reverse coordination, and inconsistent regulatory support, which hinder widespread application. Through a mixed-method approach using surveys and case studies, this study reveals barriers such as financial constraints and operational restructuring needs, while highlighting enablers like digital tools (e.g., blockchain, IoT) that enhance efficiency and transparency. Furthermore, it emphasizes the critical role of regulatory incentives (subsidies, tax breaks, and extended producer responsibility mandates) and strategic partnerships that pool resources and share risks, essential for small and medium-sized enterprises (SMEs) aiming to implement CLSCs effectively. By proposing a practical CLSC framework, informed by empirical data, this research provides actionable insights for businesses to embrace circular economy principles, aligning environmental responsibility with corporate resilience, profitability, and consumer expectations. CLSCs, therefore, are not only an environmental solution but also a strategic opportunity that addresses sustainability imperatives while meeting regulatory requirements and advancing competitive advantage.